Profil Terapi Diare Akut pada Pasien Anak Rawat Inap di Rumah Sakit Bhayangkara Surabaya - Sandra, Pipit; Hasmono, Didik; Kasih, Elisabeth; Hartono, Ruddy (Jurnal Farmasi Sains dan Terapan, 2017)
Acute diarrhea in children is defined as defecation more than 3 times per day, with changes in the consistency of feces into fluids with or without mucus and blood lasting either less than a week or up to 14 days, but not more than 14 days in children or infant. Treatment of acute diarrhea can shorten the duration of diarrhea and eradicate the organism which causes the disease. The purpose of this research was to analyze the profile of acute diarrhea treatment in hospitalized pediatric patients at Bhayangkara Hospital Surabaya including the type, dosage, route and the timing of administration which is related to the patientâ€™s medical record data. This research is an observational study in the form of retrospective study in patients with acute diarrhea with a t o t a l sampling technique. The results showed the most commonly used medications for acute diarrhea in children were parenteral rehydration fluid of KDN-1 of (41 patients, 80%) with the most widely used dose (500 cc / 4 hours â†’ 1000 cc / 24 h) IV, t h e pa t t e r n o f single antibiotic use was (43 patients, 84%), the penicillin group, ampicillin, as many as (22 patients, 44%) with the most widely used dose (4 x 250 mg) IV, the most commonly prescribed single antibiotic when discharged from the hospital was cephalosporin group, cefixime, with 17 patients (33%), with the most widely used dose (2 x 20 mg) P.O, sinbiotic with (36 patients, 70%) and the most widely used was dose (1 x 1 sachet) P.O, zinc with (49 patients, 96%) and the most widely used was dose (1 x 1 cth) P.O, vitamin A with (21 patients, 41%), and the most widely used was dose (1 x 500 IU) P.O, antidiarrhea dioctahedral smectite was (43 patients, 84%) and the most commonly used was dose (3 x 1/3 sachets) P.O.